A practical guide to video and audio compression : from sprockets and rasters to macroblocks - Wootton, Cliff (Elsevier/Focal Press, 2005)
Learn all about Codecs--how they work, as well as design and implementation with this comprehensive, easy-to-use guide to compression. After reading this book, you will be able to prepare and distribute professional audio and video on any platform including streamed to the web, broadcast on-air, stored in PVRs, Burned onto CD-ROMs or DVDs, delivered by broadband, or viewed in Kiosk applications, PDA devices, and mobile phones.